Healthcare considerations for elite dancers; Sport and exercise physicians` perspectives - Watson, J.; Hopper, L. (Journal of Dance Medicine & Science, 2026)
Introduction: Previous research on dancers` perceptions of healthcare providers and access to healthcare has found lower utilization of physicians for dance-related injuries, with the perception that dancers do not have the same access to specialized healthcare as athletes. This study is the first to examine sports and exercise medicine physicians` perspectives on similarities and differences in clinical care between dancers and athletes, specifically at the elite level.